Accessibility analysis of tools in product module interface operations. Issue 6 (19th September 2017) - Ma, Hongqin; Peng, Qingjin; Zhang, Jian; Gu, Peihua
ABSTRACT: Open-architecture product (OAP) is designed with the modular structure using personalized modules to meet different customer requirements. Different functional modules are connected to common platform modules through adaptable interfaces. This paper presents a method for the accessible analysis of tools in the interface operation to replace personalized modules of the OAP. The proposed method integrates a box-based method and the global accessibility cone with depth. Interfaces are classed and coded to meet needs of the interface management in the analysis. The tools are classified based on their access angles. An industrial paper-bag folding machine is used in the case study to verify the proposed method. GRAPHICAL ABSTRACT: